Answer:
For the given expression:
![X = ((10)/(3)) , Y = ((26)/(3))](https://img.qammunity.org/2021/formulas/mathematics/middle-school/41cuevb18onan9iv6nz9hkmx1aofpkywfb.png)
Explanation:
Here, the given expression in statement form is given as:
5 X minus Y equals 6 + negative 2 X plus Y = 8
Now, converting the given statement mathematically, we get:
5X - Y = 6 + (-2X) + Y = 8
Now, considering first and the last terms,we get:
5 X - Y = 8 .... (1)
and , considering second and the last terms,we get:
6 + (-2X) + Y = 8 or, -2X + Y = 2 ......... (2)
Adding (1) and (2) , we get:
5 X - Y - 2 X + Y = 8 + 2
or, 3 X = 10
or, X = 10/3 = 3.34
Now, 5X - Y = 8
or,
![5((10)/(3)) - Y = 8\\ \implies Y = (50)/(3) - 8 = (50 - 24)/(3) = (26)/(3) \\\implies Y = (26)/(3)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/ao3oc91g2oujtnzpvy2fqu23lily2zryfw.png)
Hence, for the given expression:
![X = ((10)/(3)) , Y = ((26)/(3))](https://img.qammunity.org/2021/formulas/mathematics/middle-school/41cuevb18onan9iv6nz9hkmx1aofpkywfb.png)